-2z(z-4)-(3z-2)=-2-(6z-2)

Simple and best practice solution for -2z(z-4)-(3z-2)=-2-(6z-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2z(z-4)-(3z-2)=-2-(6z-2) equation:


Simplifying
-2z(z + -4) + -1(3z + -2) = -2 + -1(6z + -2)

Reorder the terms:
-2z(-4 + z) + -1(3z + -2) = -2 + -1(6z + -2)
(-4 * -2z + z * -2z) + -1(3z + -2) = -2 + -1(6z + -2)
(8z + -2z2) + -1(3z + -2) = -2 + -1(6z + -2)

Reorder the terms:
8z + -2z2 + -1(-2 + 3z) = -2 + -1(6z + -2)
8z + -2z2 + (-2 * -1 + 3z * -1) = -2 + -1(6z + -2)
8z + -2z2 + (2 + -3z) = -2 + -1(6z + -2)

Reorder the terms:
2 + 8z + -3z + -2z2 = -2 + -1(6z + -2)

Combine like terms: 8z + -3z = 5z
2 + 5z + -2z2 = -2 + -1(6z + -2)

Reorder the terms:
2 + 5z + -2z2 = -2 + -1(-2 + 6z)
2 + 5z + -2z2 = -2 + (-2 * -1 + 6z * -1)
2 + 5z + -2z2 = -2 + (2 + -6z)

Combine like terms: -2 + 2 = 0
2 + 5z + -2z2 = 0 + -6z
2 + 5z + -2z2 = -6z

Solving
2 + 5z + -2z2 = -6z

Solving for variable 'z'.

Reorder the terms:
2 + 5z + 6z + -2z2 = -6z + 6z

Combine like terms: 5z + 6z = 11z
2 + 11z + -2z2 = -6z + 6z

Combine like terms: -6z + 6z = 0
2 + 11z + -2z2 = 0

Begin completing the square.  Divide all terms by
-2 the coefficient of the squared term: 

Divide each side by '-2'.
-1 + -5.5z + z2 = 0

Move the constant term to the right:

Add '1' to each side of the equation.
-1 + -5.5z + 1 + z2 = 0 + 1

Reorder the terms:
-1 + 1 + -5.5z + z2 = 0 + 1

Combine like terms: -1 + 1 = 0
0 + -5.5z + z2 = 0 + 1
-5.5z + z2 = 0 + 1

Combine like terms: 0 + 1 = 1
-5.5z + z2 = 1

The z term is -5.5z.  Take half its coefficient (-2.75).
Square it (7.5625) and add it to both sides.

Add '7.5625' to each side of the equation.
-5.5z + 7.5625 + z2 = 1 + 7.5625

Reorder the terms:
7.5625 + -5.5z + z2 = 1 + 7.5625

Combine like terms: 1 + 7.5625 = 8.5625
7.5625 + -5.5z + z2 = 8.5625

Factor a perfect square on the left side:
(z + -2.75)(z + -2.75) = 8.5625

Calculate the square root of the right side: 2.926174978

Break this problem into two subproblems by setting 
(z + -2.75) equal to 2.926174978 and -2.926174978.

Subproblem 1

z + -2.75 = 2.926174978 Simplifying z + -2.75 = 2.926174978 Reorder the terms: -2.75 + z = 2.926174978 Solving -2.75 + z = 2.926174978 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '2.75' to each side of the equation. -2.75 + 2.75 + z = 2.926174978 + 2.75 Combine like terms: -2.75 + 2.75 = 0.00 0.00 + z = 2.926174978 + 2.75 z = 2.926174978 + 2.75 Combine like terms: 2.926174978 + 2.75 = 5.676174978 z = 5.676174978 Simplifying z = 5.676174978

Subproblem 2

z + -2.75 = -2.926174978 Simplifying z + -2.75 = -2.926174978 Reorder the terms: -2.75 + z = -2.926174978 Solving -2.75 + z = -2.926174978 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '2.75' to each side of the equation. -2.75 + 2.75 + z = -2.926174978 + 2.75 Combine like terms: -2.75 + 2.75 = 0.00 0.00 + z = -2.926174978 + 2.75 z = -2.926174978 + 2.75 Combine like terms: -2.926174978 + 2.75 = -0.176174978 z = -0.176174978 Simplifying z = -0.176174978

Solution

The solution to the problem is based on the solutions from the subproblems. z = {5.676174978, -0.176174978}

See similar equations:

| (x-10)(x+4)=0 | | 3x^2+1x(-5x+4)= | | 0=x^2-2x-5 | | 7x+13=4x-17 | | -(4y+2)-(-3y-5)=-2 | | 7x+9y=11 | | ar+ar^2=9 | | 3+6p-2=5p+29-3p | | 2y+7=5y-8 | | ar+ar=9 | | 3(x-1)=4(3+3x) | | 3t+4t=42 | | 2a=r | | 8-2(4x-2)=-2 | | 2-2(6x-2)=-4 | | -10.9x=98.1 | | 4x-6+6x=5(4x-2)+2 | | 5m=-35 | | 8x+9=8(x+3) | | -13a-48=-5a | | 2.6q-3.5-5.7q=-4.1q-5.3 | | 2.6q-3.5-5.7=-4.1q-5.3 | | 4x-9y=-16 | | 7x+2=7(x-9) | | 10x+6-3=9x-2 | | 3a+5a=24 | | x^2+y^2+12x-26y+61=0 | | 4x-9y=-6 | | x+60=30 | | -5c+31=1 | | s-21=-11 | | 2(3y+1)=-16 |

Equations solver categories